Rapid Resolution of Atypical Hemolytic Uremic Syndrome by Eculizumab Treatment - Min Seung Kim; Seon Hee Lim; Ji Hyun Kim; Il-Soo Ha; Hae Il Cheong; Hee Gyung Kang (Korean Society of Pediatric Nephrology, 2020)
Atypical hemolytic uremic syndrome (aHUS) is an extremely rare and life-threatening disorder. Typical HUS is often caused by Shiga toxin-positive Escherichia coli, while aHUS is caused by dysregulation of the alternative pathway of the complement system in association with genetic abnormalities or development of autoantibodies. Eculizumab, a humanized anti-complement 5 monoclonal antibody, is recommended for the treatment of aHUS, but its long-term safety and efficacy in pediatric patients remain under review. In this paper, we report a pediatric case of aHUS with anti-complement factor H autoantibodies, who was treated successfully with eculizumab.